Probabilistic model for single and multiple action costs in maintaining both condition and safety of deteriorating reinforced concrete bridges - Aruz Petcherdchoo (Case Studies in Construction Materials, 2023)
Single and multiple cyclic maintenance actions (called essential and preventive maintenance actions) to maintain both condition and safety of deteriorating reinforced concrete bridges exposed to chloride attack are proposed to remedy the issues in the previous studies. The essential maintenance consists of Minor concrete repair (CR) and Do nothing and rebuild (RB), whereas the preventive maintenance consists of Silane treatment (SL) and Cathodic protection (CP). For these tasks, a computational platform is developed for not only determining the interaction between condition index and safety index of deteriorating bridges with maintenance, but also calculating the present value of expected maintenance costs. From the study, the combined maintenance cost of SL, CR and RB are found similar to that of CR alone in the early age, and to that of RB alone after the early age. This occurs, because the condition index of bridges with SL alone is low in the early age, whereas their safety index with SL alone is low after the early age. Moreover, the preventive maintenance by SL not only helps improve condition and safety, but also reduce the cumulative cost of combined maintenance. For applying CR or CP alone, RB is required in case that the initial condition index is below the target value for applying CR or CP. The present value of cumulative maintenance cost for the combination of CP with CR and RB is higher than that for CP alone, because more cost is added for applying CR and RB. It is not recommended to combine CP with CR or RB, because of two reasons. First, the maintenance cost of CP, CR, or RB is very high causing high cumulative cost. Second, although CP is better than SL in reducing the probability of applying CR and RB, the maintenance cost of CP is much higher than SL. Hence, SL is more appropriate than CP in combining with CR and RB. Moreover, it is advantageous to combine maintenance actions, because of two reasons. First, bridges, which have such a low condition in the early age that CR cannot be applied, can be applied after maintenance. Second, the safety of bridges is always satisfactory by applying RB. Finally, further studies are recommended.